PENGEMBANGAN MODUL ENGLISH FOR ENVIRONMENTAL ENGINEERING UNTUK MAHASISWA TEKNIK LINGKUNGAN - Saifuddin, Fahimah; Jannah, Wardatul (Penerbit Widina, Widina Media Utama, 2025)
English language skills, especially in the context of environmental engineering, are becoming increasingly crucial for environmental engineering students. However, the limited number of English learning modules that are specific and relevant to this field of study is an obstacle for students in improving their language competence. This research aims to develop an English module based on English for Environmental Engineering as a learning resource for Environmental Engineering students at Nahdlatul Ulama University of Nusa Tenggara Barat. This research and development study uses the Analysis, Design, Development, and Dissemination (ADDIE) method. The study was conducted on Environmental Engineering students at UNU NTB. The results of the student needs analysis showed that students require an English module that is thematic and relevant to their major. Subsequently, the validation phase by the expert team yielded a score of 82.3%, categorized as